Efficient Transformation of Catalpa bungei Shows Crystal Genes Conferring Resistance to the Shoot Borer Omphisa plagialis - Lv, Fenni; Wang, Peng; Zhang, Enliang; Ma, Lingling; Gao, Lulu; Yang, Rutong; Wang, Qing; Li, Ya (Frontiers in Plant Science, 2021)
Although Catalpa bungei is a forest plant with considerable economic and ornamental value in China, its wood and decorative qualities are constrained by insect pests such as the shoot borer Omphisa plagialis (Lepidoptera). Overexpressing insect resistance genes such as crystal genes to develop an insect-resistant variety of C. bungei is an environmental and ecological approach. However, genotype limitations and low regeneration rates of embryogenic calli inhibit the development of transformation and the insect-resistant gene expression system in C. bungei. Here, we first established embryogenic callus induction and regeneration systems of five genotypes using mature seed and stem segment explants; the highest induction and regeneration rates of embryogenic calli were 39.89% and 100%, respectively. Next, an efficient and stable Agrobacterium-mediated genetic transformation system was developed from embryogenic calli and its positive frequency was up to 92.31%. Finally, using the transformation system, 15 and 22 transgenic C. bungei lines that expressed Cry2A and Cry9Aa-like were generated, respectively. These transgenic lines that exhibited significantly higher resistance to O. plagialis in the laboratory and field have great promise for meeting the challenge of future pest management under changing climatic conditions. Additionally, this efficient, fast, and stable transformation system could be a potential tool for gene function analysis and forest tree genetic improvement.